Distinct expression of synaptic NR2A and NR2B in the central nervous system and impaired morphine tolerance and physical dependence in mice deficient in postsynaptic density-93 protein - Johns Roger A; Yaster Myron; Zhu Xu-Guang; Liaw Wen-Jinn; Gauda Estelle B; Tao Yuan-Xiang (SAGE Publishing, 2008)
Abstract Postsynaptic density (PSD)-93, a neuronal scaffolding protein, binds to and clusters N-methyl-D-aspartate receptor (NMDAR) subunits NR2A and NR2B at cellular membranes in vitro. However, the roles of PSD-93 in synaptic NR2A and NR2B targeting in the central nervous system and NMDAR-dependent physiologic and pathologic processes are still unclear. We report here that PSD-93 deficiency significantly decreased the amount of NR2A and NR2B in the synaptosomal membrane fractions derived from spinal cord dorsal horn and forebrain cortex but did not change their levels in the total soluble fraction from either region. However, PSD-93 deficiency did not markedly change the amounts of NR2A and NR2B in either synaptosomal or total soluble fractions from cerebellum. In mice deficient in PSD-93, morphine dose-dependent curve failed to shift significantly rightward as it did in wild type (WT) mice after acute and chronic morphine challenge. Unlike WT mice, PSD-93 knockout mice also showed marked losses of NMDAR-dependent morphine analgesic tolerance and associated abnormal sensitivity in response to mechanical, noxious thermal, and formalin-induced inflammatory stimuli after repeated morphine injection. In addition, PSD-93 knockout mice displayed dramatic loss of jumping activity, a typical NMDAR-mediated morphine withdrawal abstinence behavior. These findings indicate that impaired NMDAR-dependent neuronal plasticity following repeated morphine injection in PSD-93 knockout mice is attributed to PSD-93 deletion-induced alterations of synaptic NR2A and NR2B expression in dorsal horn and forebrain cortex neurons. The selective effect of PSD-93 deletion on synaptic NMDAR expression in these two major pain-related regions might provide the better strategies for the prevention and treatment of opioid tolerance and physical dependence.